2005
DOI: 10.1111/j.0307-6946.2005.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transgenic cotton plants on a non‐target pest, Aphis gossypii Glover

Abstract: Abstract.  1. Transgenic crops have shown great promise for the control of target pest insects, but in some cases they can also influence non‐target species. This study investigated the impact of Bt and Bt+CpTI transgenic cottons on the non‐target cotton aphid, Aphis gossypii Glover, by comparing life‐table parameters, feeding behaviour, and the fluctuating asymmetry of morphological traits of aphids reared on transgenic cotton and those on untransformed control plants.2. Aphids on the Bt+CpTI cotton showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 43 publications
0
61
0
14
Order By: Relevance
“…Liu et al [29] reported that larval growth of the cotton bollworm, Helicoverpa armigera (Hübner), was prolonged and its pupation rate and pupal weight decreased when fed on a diet containing Cry1Ac toxin. Liu et al [30] reported that aphids fed on transgenic Bt+CpTI cotton had a shorter reproduction period, longer lifespan, lower survival rate, and earlier occurrence of peak daily mortality in the first or second generation when compared with those fed on non-transgenic cotton.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [29] reported that larval growth of the cotton bollworm, Helicoverpa armigera (Hübner), was prolonged and its pupation rate and pupal weight decreased when fed on a diet containing Cry1Ac toxin. Liu et al [30] reported that aphids fed on transgenic Bt+CpTI cotton had a shorter reproduction period, longer lifespan, lower survival rate, and earlier occurrence of peak daily mortality in the first or second generation when compared with those fed on non-transgenic cotton.…”
Section: Discussionmentioning
confidence: 99%
“…In a multigeneration study, A. gossypii performed better on Cry1A-expressing cotton than on untransformed controls with a visible impact on morphological traits (Liu et al 2005). Similarly, R. padi performed better on Bt-maize in terms of fecundity with respect to control plants, though no final effect on r m was recorded (Lumbierres et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…The possible effects of Bt toxins on organisms at higher trophic levels delivered via GM plants and aphids have been described in several plantÁCry toxin systems, but the results are sometimes contrasting (Head et al 2001;Raps et al 2001;Dutton et al 2002;Lumbierres et al 2004;Liu et al 2005;Burgio et al 2007;Ramirez-Romero et al 2008;Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the continuous cultivation of Bt cotton caused obvious infestation by aphids and mealybugs in India (Losey et al 1999). Laboratory tests conducted by Liu et al (2005) showed that Aphid gossypii fed on Bt cotton had shorter reproductive duration, maximum lifespan, and an earlier peak of daily mortality in the 1st and 2nd generations compared to individuals fed on non-Bt cotton.…”
Section: Effect On the Secondary Pestsmentioning
confidence: 99%